2021
DOI: 10.1002/aelm.202100384
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in 2D Layered Mixed Sn–Pb Perovskite Thin Films for Field‐Effect Transistors

Abstract: The optoelectronic characteristics of organic–inorganic perovskites can be tailored by mixing different metal cations with various ratios. 2D layered organic–inorganic perovskites with charge transport anisotropy are considered as promising channel materials for field‐effect transistors. However, there are few reports about 2D Pb‐based perovskite thin film transistors although their Sn counterparts have been extensively investigated for use in this field. Herein, the synthesis and tuning of the physical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 79 publications
2
26
0
Order By: Relevance
“…The transfer plots (square root of current) for mobility calculations are shown in Figure S5 A. The saturation mobility ( μ ) of 0.25 ± 0.08 cm 2 V −1 s −1 , threshold voltage ( V TH ) of −21 ± 1.6 V, and on/off ratio ( I on / I off ) of 10 4 (channel length L = 160 μm, channel width W = 1000 μm) were obtained in the devices, as shown in Figure 3 C. These performance merits are similar to those reported in previous studies ( Qin et al., 2021 ; Zhang et al., 2019 ; Zhu et al., 2020b ).
Figure 3 Fabrication and characterization of (PEA) 2 SnI 4 FETs (A) Device configuration of (PEA) 2 SnI 4 BGBC FET.
…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The transfer plots (square root of current) for mobility calculations are shown in Figure S5 A. The saturation mobility ( μ ) of 0.25 ± 0.08 cm 2 V −1 s −1 , threshold voltage ( V TH ) of −21 ± 1.6 V, and on/off ratio ( I on / I off ) of 10 4 (channel length L = 160 μm, channel width W = 1000 μm) were obtained in the devices, as shown in Figure 3 C. These performance merits are similar to those reported in previous studies ( Qin et al., 2021 ; Zhang et al., 2019 ; Zhu et al., 2020b ).
Figure 3 Fabrication and characterization of (PEA) 2 SnI 4 FETs (A) Device configuration of (PEA) 2 SnI 4 BGBC FET.
…”
Section: Resultssupporting
confidence: 88%
“…Previously, Qin et al. reported the substitutional doping of (PEA) 2 SnI 4 by Pb 2+ , which leads to improved environmental stability of (PEA) 2 SnI 4 FETs but depressed hole transport owing to the larger effective mass of Pb and higher contact resistance in the devices ( Qin et al., 2021 ). Reo et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Qin et al reported that partial replacement of Sn 2+ in (PEA) 2 SnI 4 with Pb 2+ would improve the stability, although accompanied by sacrificing its electrical properties such as carrier mobility. [ 10 ] Wang et al demonstrated that Eu 2+ ion doping of (PEA) 2 SnI 4 can promote the film quality and inhibit Sn 2+ oxidation to decrease the Sn 4+ defect density. [ 11 ] In spite of these progresses, efficient and convenient methods for tuning the performance of (PEA) 2 SnI 4 FETs are still in demand.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009 when Miyasaka and co‐workers [ 1 ] first applied MHP to solar cells and realized a power conversion efficiency (PCE) of 3.8%, rapid improvements in PCE (currently up to 25.5% [ 2 ] ) have been achieved. Because of the tunable optical and electronic properties of MHPs combined with facile processing procedures, [ 3 ] applications of MHPs are no longer limited to solar cells, but have quickly extended to light‐emitting diodes, [ 4,5 ] photodetectors, [ 6–9 ] amplified spontaneous emission of lasers, [ 10–13 ] field‐effect transistors, [ 14,15 ] etc.…”
Section: Introductionmentioning
confidence: 99%
“…
cells and realized a power conversion efficiency (PCE) of 3.8%, rapid improvements in PCE (currently up to 25.5% [2] ) have been achieved. Because of the tunable optical and electronic properties of MHPs combined with facile processing procedures, [3] applications of MHPs are no longer limited to solar cells, but have quickly extended to light-emitting diodes, [4,5] photodetectors, [6][7][8][9] amplified spontaneous emission of lasers, [10][11][12][13] fieldeffect transistors, [14,15] etc. Among all possible combinations in the category of perovskite materials, triplecation perovskites, consisting of cesium (Cs + ), methylammonium (MA + ), and formamidinium (FA + ) cations at A-site in the ABX 3 structure, have gained tremendous attention.
…”
mentioning
confidence: 99%